2011
DOI: 10.1007/s10509-011-0722-x
|View full text |Cite
|
Sign up to set email alerts
|

A new class of LRS Bianchi type-II dark energy models with variable EoS parameter

Abstract: A new class of dark energy models in a Locally Rotationally Symmetric Bianchi type-II (LRS B-II) spacetime with variable equation of state (EoS) parameter and constant deceleration parameter have been investigated in the present paper. The Einstein's field equations have been solved by applying a variation law for generalized Hubble's parameter given by Berman: Nuovo Cimento 74:182 (1983) which generates two types of solutions for the average scale factor, one is of power-law type and other is of the exponenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…The directional Hubble parameters, expressing the volumetric expansion rates of the universe along the x, y and z directions respectively are (Pradhan et al 2011)…”
Section: Isotropization and Cosmological Solutionmentioning
confidence: 99%
“…The directional Hubble parameters, expressing the volumetric expansion rates of the universe along the x, y and z directions respectively are (Pradhan et al 2011)…”
Section: Isotropization and Cosmological Solutionmentioning
confidence: 99%
“…We also observe that if (81) for t = t 0 , ω = -1 (i.e. cosmological constant domi nated universe), and when t < t 0 , ω > -1 (i.e.…”
Section: Bianchi Type II Anisotropicmentioning
confidence: 54%
“…Setare [64][65][66] and Setare and Saridakis [67][68][69] have also studied the DE models in different contexts. Recently, dark energy models with variable EoS parameter have been studied by Ray et al [70], Akarsu and Kilinc [71][72][73][74], Yadav et al [75], Yadav and Yadav [76], Yadav and Saha [77] Pradhan and Amirhashchi [78,79], Pradhan et al [80][81][82], Amirhashchi et al [83][84][85][86], Kumar [87,88], Kumar and Akarsu [89], Kumar and Yadav [90] and Kumar and Singh [91]. In well known reviews on modified gravity [92,93], it is clearly indicated that any modified gravity may be represented as effective fluid with time dependent ω.…”
Section: Introductionmentioning
confidence: 99%
“…For closed universe, the Hubble parameter , H the matter energy density parameter M  and the dark energy density parameter ,   predicted by Tegmark [12] by Sahni et al [23][24].This parameter ) ( t  have been calculated with some reasoning with reduced to some simple parameterization of the dependences by many authors [25][26][27][28][29][30]. The results from SNe Ia data collaborated with CMBR anisotropy and galaxy clustering statistics (Tegmark et al [12] [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 78%